Factors Affecting Patient Satisfaction During Endoscopic Procedures - Ghazala,; -e-Hinna, Rashk; Sardar, Saman; Khan, Jahangir; Javaria,; Hassan, Fayyaz (Scripta Medica, 2024)
Background/Aim: Gastrointestinal endoscopic procedures (GEPs) are widely regarded as the premier method for assessing and treating various digestive diseases. With the rising global prevalence of endoscopic procedures, patients are becoming more discerning in selecting their endoscopists. This study aimed to identify the factors influencing patient satisfaction with endoscopic procedures.Methods: A cross-sectional study was conducted with 409 participants, out of which 212 responses were included for analysis. Exclusions were made due to contradictory answers or incomplete questionnaires. Demographic data were collected and patient satisfaction was assessed using a questionnaire. The relationship between various factors and patient satisfaction was analysed using Spearman's rank correlation.Results: The majority of patients (50.9 %) underwent endoscopy, with 59.4 % being males and 40.6 % females. The average age of the participants was 42.34 years. The study found that the most significant factors affecting patient satisfaction were waiting time to get an appointment (15.5 %), waiting time on the day of the procedure (17.0 %) and pain or discomfort during and after the procedure (15.6 %). Additionally, the personal manner of the physician and nurses, as well as comprehensive explanations before and after the procedure, were also significant factors. The study also found that certain aspects of the endoscopic procedure impacted satisfaction differently across gender and age groups. The questionnaire demonstrated strong internal consistency with a Cronbach’s alpha value of 0.917.Conclusion: This study underscores the importance of addressing waiting times, improving communication and managing patient discomfort to enhance satisfaction with endoscopic procedures. The findings provide valuable insights for improving the quality of care in endoscopy units.